Review of Marcy Meyer’s Iconographic Research Poetry - Penwarden, Sarah (Art/Research International, 2026)
In her recently published book, Iconographic Research Poetry, American researcher Marcy Meyer (2024) showcases the resonant power of metaphor by creating research poetry in/with concrete images: a tree, a juggler, a rollercoaster, a crow, a gourd. Meyer’s work shows the way in which shaped lines can echo the poem’s theme, to concentrate poetry’s power. Her work is characterised by a boldness in writing from emergence, from scenes and moments, from the way in which indigo ravens watched as she rode her bike home. Her work shows how to write ekphrasis poetry in response to epiphanies within the ordinary. She also depicts poetic writing as a collaborative conversation, in being able to offer back the poems to the maker of the object which inspired them. In this review, I also offer back some of Meyer’s own words in three found poems. Meyer’s work provides an accessible door into research poetry. It may encourage other researchers, educators, novices, and students to find their way there.